Evaluasi Program Latihan Renang terhadap Peningkatan Prestasi Atlet Usia Dini di Club Garuda Laut Makassar - Siti Nurhalizah Mutia Aulria (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This study aims to evaluate the swimming training program on improving the performance of young athletes at Club Garuda Laut Makassar. This research uses a pre-experimental method with one group pretest-posttest design involving 20 young swimmers aged 8-12 years. The evaluation was conducted over 12 weeks of structured training program consisting of technique training, physical conditioning, and mental preparation. Data collection was carried out through swimming performance tests including time measurement for 50m freestyle, 50m backstroke, and 50m breaststroke, as well as physical fitness tests including flexibility, strength, and endurance. Data analysis used paired sample t-test with significance level of 0.05. The results showed significant improvement in all measured aspects (p < 0.05). The average improvement in 50m freestyle time was 3.8 seconds (8.7%), 50m backstroke improved by 4.2 seconds (9.1%), and 50m breaststroke improved by 5.1 seconds (10.3%). Physical fitness also showed significant improvement with flexibility increasing by 15.2%, strength by 18.5%, and endurance by 22.3%. The structured training program proved effective in improving the performance of young swimmers at Club Garuda Laut Makassar.